Neural Tube Defects Trend, is COVID19 Responsible for Increased Rates? - Fatima k. Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: many studies reported the association between NTDs and maternal fever, infection like toxoplasma, rubella and cytomegalovirus, this study aimed to give the trend of the NTDs in Zakho and find if it was related to new epidemic of COVID19. Patient and method: This is study have two lines 1st studying the trend of the prevalence of NTDs depending on the health directorate statistics from Jan. 2013 to December 2021. The 2nd is a case series of 18 case of NTDs with COVID19 infection that reported in Zakho Maternity hospital labour unit. Results: The prevalence of NTD ranged from 32 during 2013 to 35 during 2017 per 10000 births, with sudden n increase to 53 per 10000 births during 2021. The case series study of 18 patient with NTDs and COVID19 infection done to uncover our doubt about the relation of COVID19 infection and NTDs. The general characteristics of mothers had baby with NTDs show that mean age of mothers was (30.5 ± 7.5) most of them from Zakho 12 (66.7%), followed by Shingar 4(22.2%). Only 2(11.1%) they married their consanguinity. Female sex of the affected baby was the common 10(55.6%), the male: female ratio was 0.8:1. Fever during the 1st trimester reported among 15(83.3%) of the patients, most of the mothers had mild COVID19 infection 14(77.8%), and 4(22.2%) had moderate severity, the antibiotics and vitamin supplement was reported among 13(72.2%). Conclusions There were increased prevalence of the NTDs in Iraq during the new epidemic COVID19 period.